2016
DOI: 10.1111/jonm.12411
|View full text |Cite
|
Sign up to set email alerts
|

Time allocation and temporal focus in nursing management: an integrative review

Abstract: These results can be used to clarify the job descriptions of nurse administrators and to plan and focus their education and training. Organisations need to use evidence to standardise the job descriptions of different levels of nurse managers and directors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 40 publications
(163 reference statements)
4
47
0
2
Order By: Relevance
“…Previous research has explored the tensions and stressors for nurse managers in clinical‐managerial hybrid roles (Burgess & Currie, ; Hewko et al, ; Labrague et al, ). However, surprisingly little is known about what nurse managers do (Bjerregård Madsen et al, ), especially their level of engagement in clinical care activities. The primary purpose of the national survey on which this paper is based was to delineate advanced practice nursing roles from other types of nursing roles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has explored the tensions and stressors for nurse managers in clinical‐managerial hybrid roles (Burgess & Currie, ; Hewko et al, ; Labrague et al, ). However, surprisingly little is known about what nurse managers do (Bjerregård Madsen et al, ), especially their level of engagement in clinical care activities. The primary purpose of the national survey on which this paper is based was to delineate advanced practice nursing roles from other types of nursing roles.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of research has demonstrated the stressors and tensions inherent in performing these clinical‐managerial hybrid roles (Burgess & Currie, ; Hewko, Brown, Fraser, Wong, & Cummings, ; Labrague et al, ). However, there is much less research on nurse managers' level of engagement in the diverse activities that comprise their roles (Bjerregård Madsen, Kaila, Vehviläinen‐Julkunen, & Miettinen, ), in particular the balance between clinical and other responsibilities. This paper addresses this gap in our understanding of nurse manager roles through a secondary analysis of data from a national survey of Australian registered nurses.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to staff nurses, nurse leaders, including nurse managers and executives, are exposed to high demands and stressors, including multiple and complex priorities with frequent interruptions, and long work hours (Bjerregård Madsen et al . ). Nurse leaders’ experiences with fatigue may also have important implications for how they view fatigue and their ability to effectively create and sustain healthy work environments within the health care system (Connaughton & Hassinger ).…”
Section: Introductionmentioning
confidence: 97%
“…As an extensive concept in various managerial domains, time management refers to a series of activities to improve time utilization rate, make effective use of time and achieve the goals of individuals or organizations (Macan, Gibson, & Cunningham, ). Effective time management contributes to better job performance, enables individuals to cope with daily work more freely and enhances job satisfaction (Belal Said, ; Bjerregård Madsen, Kaila, Vehviläinen‐Julkunen, & Miettinen, ; Kaya, Kaya, Palloş, & Küçük, ). Furthermore, time management affects personal emotion, working atmosphere and psychology to some extent (Poulin‐Tabor et al, ; Wallis et al, ).…”
Section: Introductionmentioning
confidence: 99%